2014
DOI: 10.1111/oik.01724
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of alien plant invasion on native plant communities are mediated by functional identity of resident species, not resource availability

Abstract: Alien plant invasion and nutrient enrichment as a result of anthropogenic landscape modifi cation seriously threaten native plant community diversity. It is poorly understood, however, whether these two disturbances interact with the functional identity of recipient native plants to drive community change. We performed a mesocosm experiment to examine whether the interactive eff ects of invasion by a stoloniferous turf-grass Stenotaphrum secundatum and nutrient enrichment vary across diff erent plant growth fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…The decreased community evenness was because nutrient enrichment mainly increased biomass of S. viridis and had no significant effect on biomass of other species. We found no interaction effect of H. vulgaris invasion and nutrient availability on biomass of native communities, agreeing with previous findings29. However, most previous studies have shown that plant invasion reduces community biomass414243.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The decreased community evenness was because nutrient enrichment mainly increased biomass of S. viridis and had no significant effect on biomass of other species. We found no interaction effect of H. vulgaris invasion and nutrient availability on biomass of native communities, agreeing with previous findings29. However, most previous studies have shown that plant invasion reduces community biomass414243.…”
Section: Discussionsupporting
confidence: 93%
“…As such, in the high nutrient level treatment, the native species S. viridis can capture more light before interspecific competition can suppress its growth, thus developing a higher and denser canopy than H. vulgaris and shading H. vulgaris and thereby preventing its spread39. Alternatively, the spread of stolons and root development at nodes of H. vulgaris may have been limited to vacant spaces between native plants, which were diminished by the vigorous growth of the resident root systems under high nutrient conditions29. Previous studies have suggested that root phenotypic plasticity within native communities enables native plants to persist in the context of plant invasion or changing resource levels40.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesised that receiving communities that shared functional groups with the invader would present higher invasion resistance (grass‐only communities would more strongly resist grass invaders). Gooden and French () found that the invasion of a stoloniferous grass had the strongest impact on functionally similar native species, likely due to niche overlap, so‐called limiting similarity hypothesis (MacArthur & Levins, ). However, evidence for limiting similarity in general is equivocal (Emery, ) and may be explained by narrow interpretations of functional groups or niches, phylogenetic distance, or introduction effort (Strauss et al ., ; Diez et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…[15]). A competitive advantage depends on a difference in functional identity, which is hypothesised to be involved in determining the final impact of invasion [9, 16]. The competitive advantage is, in general, ascribed to the species with the highest functional trait value, while the intensity of the advantage is defined by the difference between the functional trait values.…”
Section: Introductionmentioning
confidence: 99%